Optimizing Junior High School Students' Career Planning Through Mind Mapping-Based Group Guidance Strategies - Desy Susanti; Dona Fitri Annisa; Maya Masyita Suherman; Lulu Noorkholisoh (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2025)
This study aims to test the effectiveness of group guidance services with mind mapping techniques in improving the career planning of ninth-grade students of SMP Negeri 16 Cimahi. The research method used is a mixed method with an exploratory sequential design, combining a quantitative approach through a quasi-experimental non-equivalent control group design and a qualitative approach through interviews and observations. The study population was 189 ninth-grade students, with a sample of 17 students who had a low level of career planning, consisting of 9 students in the experimental group and 8 students in the control group. The research instrument used a career planning questionnaire that had been tested for validity and reliability (Cronbach's Alpha = 0.705), with 29 valid items out of 41 items tested. The results showed a significant increase in the experimental group, with an average pretest score of 74.9 increasing to 94.8 in the posttest. The paired sample t-test produced a significance value of 0.000 (p < 0.05) and a t-value of -11.370, which indicated a significant difference between before and after treatment. The N-Gain test showed an average value of 0.7908 or 79.08%, which is included in the high and effective category. Qualitative findings through interviews and observations strengthen the quantitative results, indicating that students experienced increased self-understanding, the ability to explore career options, and skills to develop concrete steps in career planning. This study concludes that group guidance services using mind mapping techniques are effective as a strategy to optimize junior high school students' career planning, particularly in helping students organize information visually, develop creativity, and improve a holistic understanding of their future planning. The practical implications of this study contribute to guidance and counseling teachers in developing services that are innovative, attractive, and appropriate to the developmental characteristics of junior high school students.